From Criticism toward Analytics: Commodification of Vital Goods as an Actual Research Problem in the New Economic Sociology - БердышеваЕлена Сергеевна (Journal of Economic Sociology, 2012)
The article presents a review of academic debate on commodification of vital goods in economic sociology. It is assumed that this kind of commodification ceased to be an object for continuous criticism and became a subject for active sociological research. The author describes key perspectives in studies of commodification, discloses the reasons stimulating an economic sociologists’ interest to this topic, and composes a list of relevant research issues.